A novel molecular chaperone GroEL2 from Rhodococcus ruber and its fusion chimera with nitrile hydratase for co-enhanced activity and stability. (31st December 2018) - Chen, Yangzi; Jiao, Song; Wang, Miaomiao; Chen, Jie; Yu, Huimin
Graphical abstract: Highlights: Novel R. ruber chaperones were identified by transcriptome analysis. R. ruber chaperone GroEL2 was distinguished from conventional GroEL. GroEL2 showed high self-thermal stability and protection effect on other proteins . NHase-GroEL2 fusion chimera enhanced the activity of NHase by 63.6%. It also enhanced thermal stability by 2.9× and acrylamide resistance by 1.1×. Abstract: Rhodococcus ruber harboring intracellular nitrile hydratase (NHase) is widely used in large-scale acrylamide production. Transcriptome analyses of R. ruber under urea induction and heat shock revealed the novel chaperones GroEL2 and GroES. M. jannaschii chaperone rTHS, functional in organic solvent as reported in literature, was selected as control. In vitro experiments (70 °C/90 °C incubation) showed that GroEL2 from R. ruber was highly thermostable and can stabilize other proteins as well. GroEL2 was co-expressed with NHase in E. coli in three ways: (a) monocistronic expression with one T7 promoter, (b) bicistronic expression with double T7 promoters, and (c) fusion expression with one T7 promoter driving the NHase-GroEL2 chimera. Experimental results showed that the NHase-GroEL2 chimera was the most successful expression strategy. Maximal NHase activity was enhanced by 63.6% compared with the single NHase control. A stability assessment showed that the residual activity levels after heat shock and acrylamide (AM) immersion increased by 2.9× and 1.1×, respectively. For the fusion chimeras NHase-GroES and NHase-rTHS, their thermal stability also significantly enhanced by 1.6× and 64.0%, respectively; but their AM resistance both reduced (36.2% and 29.0%, respectively). In vivo heat inactivation curves further confirmed thermal stability enhancement of NHase by chaperone fusion, in which NHase-GroEL2 was the most stable one. Its inactivation constant kd was only ∼1/4 that of the single NHase. The K cat of the intracellular NHase-GroEL2 was also remarkably higher than that of the NHase control.